Aktivitas Antibakteri dan Antioksidan Kulit Apel Rome Beauty (Malus sylvestris Mill) - Aldesra Fitri; Ardika Amanda Silya; Olafiani Ryhasanda; Fendi Yoga Wardana; Mayang Aditya Ayuning Siwi (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2026)
Rome beauty apple (Malus sylvestris Mill) is an apple variety that is widely grown in Batu City. The skin of this apple is known to contain flavonoid compounds such as quercetin, catechin, procyanidin and caffeic acid which are useful as antibacterial, antioxidant, and antiproliferative. This study was conducted to determine the total flavonoid content and antibacterial activity in the ethanol extract of macerated Roma beauty apple peel. In addition, this study also aims to determine the antioxidant activity of the ethyl acetate extract and the ethanol extract of Roma beauty apple from multistage extraction. The ethanol extract of macerated Rome beauty apple was tested for total flavonoid content and antibacterial activity using the well diffusion method, then the diameter of the inhibition zone was measured against Propionibacterium acnes and Staphylococcus aureus bacteria, while the ethyl acetate extract and the ethanol extract of Rome beauty apple from multistage extraction were tested for antioxidant activity using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. Based on the research, it is known that the ethanol extract of Rome Beauty apple peel from maceration contains flavonoids of 47.10 mgQE/g with an inhibition zone diameter against Propionibacterium acnes and Staphylococcus aureus of 8.70 mm and 11.67 mm respectively with a concentration of 20% w/v. The results of the antioxidant activity test of the ethyl acetate extract obtained IC50 3026 ppm and the ethanol extract from multistage extraction of 4702 ppm. The test results can be concluded that the ethanol extract of Rome Beauty apple has a total flavonoid content and antibacterial activity with a moderate category against P. acnes bacteria and strong against S. aureus bacteria. The ethyl acetate extract and the ethanol extract of Rome Beauty apple peel from multistage extraction have antioxidant activity with a very weak category.